Species‐specific water use by woody plants on the Edwards Plateau, Texas. Issue 2 (29th November 2012) - Elkington, R. J.; Rebel, K. T.; Heilman, J. L.; Litvak, M. E.; Dekker, S. C.; Moore, G. W.
ABSTRACT Woody encroachment is of great socio‐economic and ecological importance in semiarid savannas because it is presumed to alter the water balance in such ecosystems. We compared two encroachers, Ashe juniper (Juniperus ashei) and honey mesquite (Prosopis glandulosa), with the less invasive live oak (Quercus fusiformis) to ascertain whether soil depth or species‐specific water use strategy is most important in determining transpirational losses on shallow soils underlain by fractured limestone bedrock on the Edwards Plateau. Sap fluxes, leaf water potentials, soil moisture and meteorological information were monitored during spring 2009 at three sites with differing soil depths and were used in a non‐spatial soil–vegetation–atmosphere water transfer model to predict different rooting depths. Sap flux responses and soil water stress were compared using multivariate statistical analysis. At two relatively deep‐soil savanna sites, we found that dominant tree species had similar water use behaviour. However, at the shallow‐soil forest containing Ashe juniper and live oak, juniper transpiration was much higher early in the season than oak transpiration, indicating that juniper benefited more from early spring rainfall than oaks. The model predicts that maximum rooting depths for the woody vegetation were mostly constrained by site soil depths. This study provides new evidence that these species perform similarly on shallow soils and that their water use is restricted by soil depth. The only species‐specific strategy found important in determining transpirational losses was juniper's ability to withstand low soil water potentials in very shallow soils. Copyright © 2012 John Wiley & Sons, Ltd.